Conceptual development of a dynamic underwater acoustic channel simulator - Caley, Michael; Duncan, Alexander (The Australian Acoustical Society, 2011)
The underwater acoustic communication channel is characterised by transient signal fading across multiple propagation paths and much greater time spread between first and last arrivals than in terrestrial wireless systems. At useful transmission distances of a few kilometres the channel is significantly bandwidth-limited in the tens of kHz by absorption at higher frequencies, and unlike most terrestrial wireless radio-frequency channels, relative transmitter/ receiver motion and sea-surface motion leads to significant signal Doppler effects. A dynamic underwater acoustic channel simulator is being developed to test and improve the effectiveness of point-to-point signal transmission by underwater acoustic modem systems. The simulator will enable testing of modems and signalling strategies in diverse transient acoustic propagation and background noise conditions in a cost-effective manner. The purpose of this paper is to outline the modelling challenges that are being addressed.